2013
DOI: 10.1016/j.jpainsymman.2012.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Based Dyspnea Self-Management Support for Patients With Chronic Obstructive Pulmonary Disease

Abstract: Context People with chronic obstructive pulmonary disease (COPD) experience dyspnea with activities despite optimal medical management. Objectives The purpose of this study was to test the efficacy of two 12-month dyspnea self-management programs, Internet-based (eDSMP) and face-to-face (fDSMP), compared with a general health education (GHE) control on the primary outcome of dyspnea with activities. Methods Participants with COPD were randomized to eDSMP (n=43), fDSMP (n=41) or GHE (n=41). The content of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
169
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(174 citation statements)
references
References 36 publications
1
169
1
3
Order By: Relevance
“…In addition, among older adults, the relationship between self-efficacy for safe-sex behaviors was influenced by perceived effectiveness to perform safer sexual behaviors (Foster et al, 2012). In that study, as well as other studies focused on management of chronic illness, educational interventions have been shown to improve the self-efficacy in older adults (Beverly et al, 2013;Nguyen et al, 2013).…”
Section: Theoretical Modelmentioning
confidence: 81%
“…In addition, among older adults, the relationship between self-efficacy for safe-sex behaviors was influenced by perceived effectiveness to perform safer sexual behaviors (Foster et al, 2012). In that study, as well as other studies focused on management of chronic illness, educational interventions have been shown to improve the self-efficacy in older adults (Beverly et al, 2013;Nguyen et al, 2013).…”
Section: Theoretical Modelmentioning
confidence: 81%
“…The review provided by Marschollek and colleagues (2007), although focused on elderly individuals, did not identify studies on patient populations with a mean age of 65 years and older. While a more recent review by Stellefson and colleagues (2013) included three studies with patient populations of 65 years and older, only Web 2.0 (social media) self-management interventions were examined (Bond et al, 2010;Nguyen et al, 2008;Nguyen et al, 2013). Consequently, few evidence-based guidelines exist for the development of effective OHITs for older patients.…”
mentioning
confidence: 99%
“…Nach der Intervention haben sich die Selbstwirksamkeit als psychische Ressource und die körper-liche Leistungsfähigkeit als physische Ressource der Patienten signifikant verbessert [40,41]. In einem systematischen Review über webbasierte Interventionen zur Verbesserung der körperlichen Aktivität sowie des Empowerments der Patienten mit chronischen Erkrankungen schlussfolgern die Autoren, dass sowohl Wissensvermittlung, Selbstbeobachtung und Kommunikation mit medizinischen Personal oder Betroffenen als auch Selbstmanagementtraining und individuelle Übungsprogramme förder-liche Interventionsinhalte sind [26].…”
Section: Infoboxunclassified